Turning Points during the U.S. Civil War: Views from the Grayback Market - Marc D. Weidenmier (Claremont McKenna College, Department of Economics, 1999)
This paper introduces a new high frequency time series of Confederate money prices taken from the newspapers of Richmond and leading cities in the Eastern Confederacy. The new Grayback series is tested for "turning points." The empirical analysis suggests that "turning points" in the Confederate Grayback market were different from those identified in the Union Greenback market by Willard et al. (1996). It appears that war did not always have symmetric effects on Northern and Southern money prices.
Keywords: N20; N40; 330; Confederacy; turning points